Development of Functional Thinking-Based Student Worksheets to Improve Mathematical Generalization Abilities - Suryowati, Eny; Aini, Nurul (Jurnal Pendidikan MIPA, 2025)
This study aims to develop valid, practical, and efficient functional thinking-based student worksheets to improve students' mathematical generalization abilities. This study used a 4D development research approach, divided into four stages: Defining, Designing, Developing, and Disseminating. Thirty-eight-grade students of class VIII H MTsN 9 Jombang became the subjects of this study. The research instruments were validation sheets, teachers’ response questionnaires, students’ response questionnaires, interview guidelines, and test questions. This functional thinking-based worksheet was designed based on functional thinking indicators. Functional thinking in this research consists of recursive patterns, covariational thinking, and correspondence relationships. The data analysis results showed that the functional thinking-based student worksheets developed have a validity score of 87,5% from teachers and 90% from lecturers, categorized as very good (valid). The results of the teacher response questionnaire were 80%, and the student response questionnaire was 82,25%, both classified as good. The average pre-test score was 53, and the average post-test score was 75. N-gain scores for each indicator of mathematical generalization ability in the medium and high categories. It is found that there was an increase in students’ generalization ability. Generalization ability studied includes perceptions about generalization, expressions of generalization, formulating generalities symbolically, and solving problems using the results of generalization. The most prominent finding in this study is the improvement in the ability to formulate generalities symbolically. This indicates that the use of functional thinking-based worksheets is sufficiently effective in enhancing students' generalization ability. The results of this study provide theoretical implications for how to improve students' generalization ability.    Keywords: functional thinking, student worksheets, mathematical generalization ability.